2013
DOI: 10.1002/mnfr.201300010
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of hydroxytyrosol on liver ischemia/reperfusion injury in mice

Abstract: HT exerts protective effects against hepatic I/R injury in mice, which might be associated with its anti-oxidative, anti-inflammatory, and anti-apoptotic properties. HT may be an effective hepatoprotective agent and a promising candidate for the treatment of liver I/R injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 33 publications
(58 reference statements)
1
45
0
Order By: Relevance
“…It has been demonstrated that the activation of Kupffer cells, production of cytokines, cell adhesion factor, and reactive oxygen species (ROS) play a pivotal role in the pathogenesis of hepatic I/R injury [6, 7]. The main pathological changes of hepatic I/R injury are the neutrophil infiltration and liver cell death caused by diverse factors.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the activation of Kupffer cells, production of cytokines, cell adhesion factor, and reactive oxygen species (ROS) play a pivotal role in the pathogenesis of hepatic I/R injury [6, 7]. The main pathological changes of hepatic I/R injury are the neutrophil infiltration and liver cell death caused by diverse factors.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that PF is able to increase SOD levels in ischemic brain tissue, and reduce MDA content (27). In addItion, it has been suggested that PF inhibits the production of free radicals, improves SOD activity in the brain, and decreases MDA content following cerebral ischemia; therefore protecting secondary neurons from injury (15,28,29). PF has a strong anti-inflammatory effect, which has been shown to reduce the enhanced phagocytic function of peritoneal macrophages in rheumatoid arthritis models, and lower levels of TNF-α, IL-1 and IL-6 (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…A similar study with ambroxol, proved its protective action against hepatic IR injury via attenuation of JNK activation and lowering of Bax, Bcl‐2 and caspase‐3 expressions . Likewise, hydroxytyrosol, a phenolic compound from the olive oil has been shown to execute its sentinel role against hepatic IR, by lowering the levels of TNF‐α, IL‐6, macrophage inflammatory protein‐2 and inhibiting the ROS‐ induced oxidative damage in liver . Huperizine A, an alkaloid from Huperzia serratia , a widely used plant in chinese traditional medicine has been reported to exert anti‐apoptotic role through down regulation of Bax/Bcl2 ratio, and caspase‐3expression in rat model of hepatic IR with portal and bile duct clamping …”
Section: Introductionmentioning
confidence: 84%